2016
DOI: 10.1111/hel.12308
|View full text |Cite
|
Sign up to set email alerts
|

Xenobiotic Pathway Gene Polymorphisms Associated with Gastric Cancer in High Risk Mizo‐Mongoloid Population, Northeast India

Abstract: Presence of H. pylori with CagA genotype showed significant individual effect with GSTT1 polymorphism as well as strong synergistic effect in gastric cancer risk. Majority of the gastric cancer samples showed significant negative expression in G/G, A/G (rs1695), and T/T (rs1138272) genotypes. This study shows that GST gene polymorphism was significantly relevant for determining the individual susceptibility to gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Some members under this genus are pathogenic and found to cause peptic ulcers, gastritis, and stomach cancer (Yamaoka 2008 ). This is a significant risk factor for high incidence of stomach cancer among the populace of Mizoram (Ghatak et al 2016 ). Identified bacterial genera possibly involved in fermentation of sa - um were Kouria , Lactobacillus , B. coagulans , Collinsella , and Coprococcus .…”
Section: Discussionmentioning
confidence: 99%
“…Some members under this genus are pathogenic and found to cause peptic ulcers, gastritis, and stomach cancer (Yamaoka 2008 ). This is a significant risk factor for high incidence of stomach cancer among the populace of Mizoram (Ghatak et al 2016 ). Identified bacterial genera possibly involved in fermentation of sa - um were Kouria , Lactobacillus , B. coagulans , Collinsella , and Coprococcus .…”
Section: Discussionmentioning
confidence: 99%
“…An additional 56 articles were excluded, including 56 articles with unavailable data on the genotype frequency of CC, CT, and TT within GSTP1 rs1138272, and 4 articles in which the data were not in HWE. After a quality evaluation, 40 articles (Harris et al, 1998; Saarikoski et al, 1998; Park et al, 1999; Wadelius et al, 1999; Welfare et al, 1999; Marshall et al, 2000; Stanulla et al, 2000; Krajinovic et al, 2002; Wang et al, 2003, 2011; Sorensen et al, 2004; Yang et al, 2004; Garcia-Closas et al, 2005; Landi et al, 2005, 2007; Moore et al, 2005; De Roos et al, 2006; Lira et al, 2006; Marciniak et al, 2006; Jiao et al, 2007; Li et al, 2007, 2010; Murphy et al, 2007; Al-Dayel et al, 2008; Kury et al, 2008; Siraj et al, 2008; Van Emburgh et al, 2008; Zienolddiny et al, 2008; Canova et al, 2009; Northwood et al, 2010; Sainz et al, 2011; Ebrahimkhani et al, 2012; Garcia-Gonzalez et al, 2012; Ibarrola-Villava et al, 2012; Dura et al, 2013; Oskina et al, 2014; Ghatak et al, 2016; De Mattia et al, 2017; Minina et al, 2017; Rajesh et al, 2018) of good quality were included. Finally, we included a total of 43 case-control studies for our quantitative synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…We removed one case-control study in which the data were not in HWE (Marie-Genica Consortium on Genetic Susceptibility for Menopausal Hormone Therapy Related Breast Cancer Risk, 2010), and we removed two additional studies (Barnette et al, 2004) because they failed to meet the requirement of reporting the genotype frequency in both the case and control group. Moreover, 17 new articles (Park et al, 1999; Welfare et al, 1999; Marshall et al, 2000; Stanulla et al, 2000; Krajinovic et al, 2002; De Roos et al, 2006; Lira et al, 2006; Li et al, 2007, 2010; Sainz et al, 2011; Garcia-Gonzalez et al, 2012; Dura et al, 2013; Oskina et al, 2014; Ghatak et al, 2016; De Mattia et al, 2017; Minina et al, 2017; Rajesh et al, 2018) were added. Finally, a total of 40 articles were included in our updated meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the SNP in GSTP1 gene resulting in amino acid substitutions at codon 105 (Ile→Val) is also associated with reduced detoxifying activity of the GST enzyme and cancer risk but less studied in premalignant gastric lesions. Many studies showed that the polymorphic variants of GSTT1 , GSTM1 , and GSTP1 genes were associated with increased risk for gastric cancer, especially in the Asian population [ 13 , 21 23 ]. However, certain studies performed in the European population sustained that the GST gene polymorphisms are not relevant in gastric cancer [ 15 ].…”
Section: Discussionmentioning
confidence: 99%